Complete mitochondrial genome for the whitemouth croaker Micropogonias furnieri (Perciformes: Sciaenidae). Issue 12 (2nd December 2021) - Kim, Kang-Rae; Kim, Yong Hwi; Park, Jong Yeon; Han, Ho-Seop; Bang, In-Chul
Abstract: This study is the first to research to report the complete 16, 496 bp mitochondrial genome of Micropogonias furnieri, which consists of 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and a control region (D-loop). The overall base composition of the complete genome is 27.26% A, 25.65% T, 16.46% G, and 30.63% C, with a high A + T content of 52.91%. Phylogenetic analysis showed that M. furnieri was most closely related to Sciaenops ocellatus . In this study, the mitogenome of M. furnieri will provide useful information for phylogenetic and evolutionary understanding in the family Sciaenidae.